2007
DOI: 10.1007/s00586-007-0351-9
|View full text |Cite
|
Sign up to set email alerts
|

Complications of anterior cervical discectomy and fusion using recombinant human bone morphogenetic protein-2

Abstract: The use of bone morphogenetic protein-2 (rhBMP-2) in spinal fusion has increased dramatically since an FDA approval for its use in anterior lumbar fusion with the LT cage. There are several reports of its use in transforaminal lumbar interbody fusion, posterolateral fusion, and anterior cervical fusion. Reports on adverse effects of rhBMP-2 when used in spinal fusion are scarce in literature. An Institutional Review Board approved retrospective study was conducted in patients undergoing anterior spinal fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
152
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(157 citation statements)
references
References 22 publications
1
152
0
1
Order By: Relevance
“…Since clinical data demonstrate a host response to rhBMP-2 after implantation, 13,14,17,27,28 four animals in the TrioMatrix 1 and rhBMP-2 groups underwent a modification of the posterolateral arthrodesis protocol followed by magnetic resonance imaging (MRI) evaluation of the lumbar spine to assess localized host response during the bone healing process at the 7-day time point. 29 In addition to arthrodesis, 1.06 AE 0.17 cc 3 of paraspinal muscle compartment was excised bilaterally to create an adjacent space next to the site of fusion.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Since clinical data demonstrate a host response to rhBMP-2 after implantation, 13,14,17,27,28 four animals in the TrioMatrix 1 and rhBMP-2 groups underwent a modification of the posterolateral arthrodesis protocol followed by magnetic resonance imaging (MRI) evaluation of the lumbar spine to assess localized host response during the bone healing process at the 7-day time point. 29 In addition to arthrodesis, 1.06 AE 0.17 cc 3 of paraspinal muscle compartment was excised bilaterally to create an adjacent space next to the site of fusion.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…RhBMP-2 is approved by the U.S. Food and Drug Administration for limited select indications. However, the high cost of rhBMPs, the variability of its efficacy in humans, and recent reports of serious side effects associated with its use are important factors limiting its clinical utility [8][9][10][11] . The systemic delivery of a therapeutic agent that can enhance bone repair in fractures and nonunions is an attractive option because it does not involve any surgery, can be administered to the patient in the office setting, and may allow for prolonged and frequent dosing 1 .…”
mentioning
confidence: 99%
“…Dodd et al conducted a case-control study of the use of autografts versus allografts which were from femoral heads in the surgery of idiopathic adolescent scoliosis. They reported that there was no difference, either in a Baskin et al [7] A prospective pilot trial for the use of rhBMP-2/collagen sponge with a fibular allograft and anterior cervical plate Shields et al [79] Retrospective review of patients who underwent an anterior cervical fusion using high-dose rhBMP-2/collagen sponge Vaidya et al [98] Retrospective review of patients undergoing anterior cervical spinal fusion and instrumentation…”
Section: Allograftsmentioning
confidence: 99%